Conhecimentos estatísticos no Ciclo I do Ensino Fundamental: um estudo diagnóstico com professores em exercício - Bifi, Carlos Ricardo (2014)
The purpose of this study was to diagnose the modes of functioning of pedagogical and mathematical knowledge held by a group of primary school teachers (1st to 5th grades) in Brazil. The investigation sought to identify elements that signaled these teachers perceptions of their knowledge of Statistics, Probability, and Combinatorics for the primary school curriculum. The question that guided the investigation was: Which aspects of pedagogical and specific statistical knowledge are mobilized in situations of class design and management by a group of teachers during their teaching practices? Nine teachers participated in the study, one of whom, who had received specific training (Teaching Degree in Mathematics) and held a Master s Degree in Science and Mathematics Teaching, spontaneously stood out as the group leader. This case study was developed in three stages, using the following instruments: observation of discussions in periods officially allotted to collective pedagogical work, observation of the teachers practice during lessons addressing the block of contents termed Treatment of information , and interviews. The first two stages guided the construction of a set of activities that formed the basis for the interviews. The data thus collected revealed the pedagogical and specific knowledge related to the Treatment of information block to be insufficient for the teachers to meet the needs of students findings that converge with those from investigations in Statistics Education. The behavior of the group leader ensured some sort of continuing education to the other members, raising their awareness of the effectiveness of collaborative work and socialization of their knowledge. In some sessions, the group admitted their own lack of knowledge on topics proposed for discussion e.g., Probability and fractions. The results indicated the importance of working collectively and investing in training or mentoring, beyond the hours officially allotted to collective pedagogical work, so as to foster the construction of pedagogical and specific knowledge related to Statistics, Probability, and Combinatorics by these teachers. Also identified was the need for providing teachers with training capable of empowering them (by constructing knowledge) to the use and complementation of teaching materials, textbooks, and other materials available in the school. Additional specific investigation should elucidate the functioning mode of the knowledge held by the participants, given the noteworthy specific features of the modes detected in the group features not fully described by the theoretical framework adopted. Further research is required to map more thoroughly these novel features detected in knowledge functioning modes